Multispectral optoacoustic tomography for in vivo detection of lymph node metastases in oral cancer patients using an EGFR-targeted contrast agent and intrinsic tissue contrast: A proof-of-concept study - Vonk, J.; Kukacka, Jan; Steinkamp, P. J.; De Wit, J. G.; Voskuil, F. J.; Hooghiemstra, W. T. R.; Bader, M.; Juestel, D.; Ntziachristos, V.; Van Dam, G. M.; Witjes, M. J. H. (Photoacoustics, 2022)
Oral cancer patients undergo diagnostic surgeries to detect occult lymph node metastases missed by preoperative structural imaging techniques. Reducing these invasive procedures that are associated with considerable morbidity, requires better preoperative detection. Multispectral optoacoustic tomography (MSOT) is a rapidly evolving imaging technique that may improve preoperative detection of (early-stage) lymph node metastases, enabling the identification of molecular changes that often precede structural changes in tumorigenesis. Here, we characterize the optoacoustic properties of cetuximab-800CW, a tumor-specific fluorescent tracer showing several photophysical properties that benefit optoacoustic signal generation. In this first clinical proof-of-concept study, we explore its use as optoacoustic to differentiate between malignant and benign lymph nodes. We characterize the appearance of malignant lymph nodes and show differences in the distribution of intrinsic chromophores compared to benign lymph nodes. In addition, we suggest several approaches to improve the efficiency of follow-up studies.
CRIS-Team Scopus Importer:2023-03-08